Determinants of Rural Out-Migration at Household Level: Logistic Regression Analysis - Aryal, Tika Ram (Economic Journal of Nepal, 2005)
The main aim of this paper is to investigate the determinants of migration at household level according to the background characteristics of family. The data are taken from a sample survey of Palpa and Rupandehi districts. Logistics regression technique was utilized to identify the influential factors in the migration process. The findings indicate that the risk of out-migration was higher for the households attaining at least primary level of education, having occupation other than agriculture and labour workers, landless and marginal landholdings, having more than one adult male members, having family size more than three members and Newar/Gurung/Magar caste/ethnicity category. Economic Journal of Nepal Vol.28(3) 2005 pp.169-177